Doubling farmers' income : Scenario, challenges, opportunities and the way forward: DOUBLING FARMERS' INCOME : SCENARIO, CHALLENGES, OPPORTUNITIES AND THE WAY FORWARD - V RANGA RAO (Journal of Oilseeds Research, 2019)
The country's farm sector, the lifeline of economy, has been of late in the throes of a very paradoxical situation namely its shrinking share in country's GDP amidst dependence of close to 60% of country's population on it for their livelihood worsening the agrarian distress and the associated high farmer suicides every year in the face of spectacular performance on the production and productivity front in the form of 'green', 'blue' 'yellow' 'white' revolutions. The average income ofmore than 60% offarm households in the country with less than one hectare land is hardly a fourth of the current national average per capita income. While no doubt, the farm sector today offers a plethora of avenues for stepping up aggregate production as well as productivity of agri-horti, animal, fish, bird per unit area, input, time and effort, banishing current agrarian distress coupled with doubling farmers' incomes may however, continue to be a vision in spite of all such isolated and fragmented efforts. The paper therefore, calls for an integrated multi-pronged, multi-dimensional initiativesinvolving production as well as post production chain for translating not only PM's vision into reality at ground level but liberate the much distressed sections of the farm sector, i.e. the millions ofsmall and marginal farmers of the society fromtheir chronic vulnerabilities to weather and market risks, poverty, indebtedness, structural inefficiencies, adverse terms of trade, anti-farmer farm policies, rampant supplies of spurious and substandard inputs and thru it transform their lives and economies.